PREVALENCE OF LOW BACK PAIN AMONG PRIVATE MIDDLE SCHOOL CHILDREN IN HAYATABAD - Khattak, Saadia; Mazhar, Sajida; Khan, Danish Ali; Jan, Mohammad Bin Afsar (Annals of Allied Health Sciences, 2017)
AIM: The objective of this study was to determine prevalence of Iow back pain among private middle school children in Hayatabad. METHODS: A total of 613 students with age group between 11 to 15 years participated in the study. They were evaluated with Pre Shaded Minikin, Low Back Pain Symptom Characteristics and Modified Hanover Low Back Pain Disability Questionnaires. RESULTS: Chi square test was used for the statistical analysis of the data. The period prevalence of low back pain was found 41.1%. Among those with LBP, 94.0% of the participants reported that Low back pain lasts for <12h, 48.8% of the participants reported score 4 on faces scale, 8.3% of the participants reported radiating pain down the leg whereas medical consultation was reported by only 7.9% of the participants. There was no significant difference between boys and girls. On Modified Hanover Low Back Pain Disability Questionnaires, less number of children reported severe limitations in activities. About 63.1% of the participants reported activity limitations by sitting on a school chair for a 45 minute lesson, whereas 62.3% of the participants reported pain in carrying school bag activity. CONCLUSION: Time prevalence of low back pain is high in school children and medical constancy remained ignored in majority of the cases